(untitled) (Proceedings of Southern Federal University. Philology, 2014)
Key words: autobiographical pact, self-knowledge, auto fiction, reality, fiction, modern French literature. Autofiction is one of the dominant trends in the development of modern French prose. The term was proposed by S. Dubrovsky in the late 1970s and was extremely tempting for writers who wanted to join the «auto» and «fiction», to give artistic form to documentary storytelling. In recent decades the term has acquired a broad interpretation and attracted a wide variety of writers: Gary Michon, Sollers, Welbeck, Beigbeder, Modiano, Duras, Le Clezio, Erno, etc., which are constructing in their works an endless “Lego from ego”. If in the early years of creativity are dominated by a fictional component, that many later moving to strengthen the documentary to the autobiography, which is currently taking on the traits of artistry. Autofiction is widely studied in France, where regular conferences are held and it is published collections of papers and monographs. The article on the basis of analysis and critical literature distinguishes features of this new genre, demanded not only in France, it is identified certain trends in its development.